Anionic Metal–Organic Framework for Selective Dye Removal and CO2 Fixation. Issue 27 (27th April 2016) - Kumar, Sanjay; Verma, Gaurav; Gao, Wen‐Yang; Niu, Zheng; Wojtas, Lukasz; Ma, Shengqian
Abstract : A microporous Zn‐based anionic metal–organic framework (MOF) was synthesized with triangular 4, 4′, 4′′‐(pyridine‐2, 4, 6‐triyl)tribenzoic acid. The anionic MOF material featuring open channels proved to be a good capturing agent for the cationic dye methylene blue. In addition, the Zn‐MOF demonstrated excellent catalytic activity for CO2 fixation by cycloaddition reaction with epoxides for the generation of cyclic carbonates. Abstract : A microporous Zn‐based anionic metal–organic framework (MOF) is synthesized with triangular 4, 4′, 4′′‐(pyridine‐2, 4, 6‐triyl)tribenzoic acid; it features open channels and proves to be a good capturing agent for cationic dyes. In addition, the Zn‐MOF demonstrates excellent catalytic activity for CO2 fixation by cycloaddition reaction with epoxides.